Wolontariat na obszarze globalnego Południa. Organizacje i obszar ich działalności - Jarosz, Jacek (Studia Edukacyjne, 2023)
The work of organizations engaged in social activities is an example of a solidarity-based response to some of the vital problems of the modern world. Polish entities involved in such activities include non-governmental organizations (mainly foundations and associations) and church organizations. The area of work for some of them is the so-called global South. The article aims to indicate which entities offer participation in volunteering in the global South and to identify those that engage in volunteering dedicated to educational activities. The achievement of this goal will e.g. enable more detailed research on the activities of various entities in the global South. This article presents theoretical considerations related to attempts to divide the world into the global North and global South, as well as the types of Polish entities undertaking broadly defined social activities. It also presents a list of entities that offer Poles to participate in volunteering in the global South with an indication of the thematic areas of volunteer activities.